Validation of the Chinese version of Brief Assessment of Cognition in Schizophrenia - Wang LJ; Lin PY; Lee Y; Huang YC; Hsu ST; Hung CF; Chen CK; Chen YC; Wang YL; Tsai MC (Neuropsychiatric Disease and Treatment)
Liang-Jen Wang,1 Pao-Yen Lin,2,3 Yu Lee,2 Yu-Chi Huang,2 Su-Ting Hsu,4 Chi-Fa Hung,2 Chih-Ken Chen,5,6 Yi-Chih Chen,5,6 Ya-Ling Wang,2 Ming-Che Tsai2 1Department of Child and Adolescent Psychiatry, Kaohsiung Chang Gung Memorial Hospital and Chang Gung University College of Medicine, 2Department of Psychiatry, Kaohsiung Chang Gung Memorial Hospital and Chang Gung University College of Medicine, 3Institute for Translational Research in Biomedical Sciences, Kaohsiung Chang Gung Memorial Hospital, 4Department of Community Psychiatry, Kaohsiung Municipal Kai-Syuan Psychiatric Hospital, Kaohsiung, 5Department of Psychiatry, Chang Gung Memorial Hospital, Keelung, 6Chang Gung University College of Medicine, Taoyuan, Taiwan, Republic of China Objective: A test battery that measures cognitive function impairment in patients with schizophrenia, the Brief Assessment of Cognition in Schizophrenia (BACS), has been translated into various languages and validated. This study aimed to test the reliability and validity of the Chinese version of the BACS in a Chinese-speaking population. Methods: All participants in this study (66 patients with schizophrenia [mean age: 41.2 years, 57.6% male] and 66 age- and sex-matched healthy controls) were from Taiwan and assessed using the BACS and the University of California, San Diego (UCSD) Performance-Based Skills Assessment, Brief Version (UPSA-B). Thirty-eight of the 66 patients with schizophrenia received a reassessment using the BACS. Results: The BACS had good test–retest reliability, and all BACS subtests had statistically insignificant practice effects. Principal components analysis demonstrated that a one-factor solution best fits our dataset (60.9% of the variance). In both patients and controls, the BACS composite scores were positively correlated with all BACS subscales (P<0.001) and UPSA-B scales (P<0.001). Furthermore, all BACS subtests (verbal memory, working memory, motor speed, verbal fluency, attention and processing speed, and executive function) significantly differentiated patients with schizophrenia from healthy controls (P<0.001), and the BACS composite score had the best discriminative validity (P<0.001). Conclusion: The Chinese version of the BACS exhibits satisfactory psychometric properties, including high test–retest reliability, high internal consistency, acceptable concurrent validity, and good discriminant validity. We suggest that the BACS is a reliable and practical tool for assessing cognitive function in patients with schizophrenia. Keywords: psychometrics, reliability, validity, cognitive function, schizophrenia